Product Quality of Domestic Dual Purpose Hybrid Chickens under Conditions of Private Households - Pankova, Svetlana; Katerynych, Oleg (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Shows the results of the assessment of the quality of meat and eggs of a new Ukrainian hybrid of a dual purpose, obtained by crossing a native breed hens “Poltavska glinyasta“ with cocks of factory line G2 white “Plymouth Rock“ breed of domestic selection are presented. As a result, fattening cockerels during 12 weeks and their slaughter at the end of the experiment found a statistically significant advantage of hybrid young over the maternal form of live weight (53.7%), eviscerated carcass weight (60.7%), the output of an eviscerated carcass (3.1%) and muscle tissue (72%). For the chemical constituents hybrids meat is not inferior to the original form. Analysis of the physical and morphological indicators of eggs showed a significant advantage (P >0.999) of the hybrid bird over the maternal line at the age of 30 weeks by the eggs weight (57.9 and 54.1 g), yolk weight (16.2 and 14.3 g) and the energy value of eggs (155.3 and 148.6 kcal). At 49 weeks of age egg quality parameters hybrid were at the level of parental forms – egg weight 67.2 g, the contents of the yolk in eggs 30.5%, the ratio of albumin to the yolk – 1.9, indicating a high energy value of the product – 162 8 kcal per 100 g of egg mass. Thus, showed the double (combined) type of productivity of hybrid, which uses of is aimed at obtaining meat (with fattening cockerels) and eggs (while keeping hens) high quality.